TINGKAT KEPENTINGAN DAN KEPUASAN. KONSUMEN "FREE STANDING OPERATION RESTAURANT" - I Nyoman Arcana (JURNAL KEPARIWISATAAN, 2011)
The aim of this study was to investigate the elements of marketing mix (Morrison, 2002) which comprised of product, price, place/distribution, promotion, people, programming, packaging, and partnership (8Ps) of the free standing restaurants in Ubu, Bali. Data were collected by distributing questionnaires to guests who had their meals in the restaurants in Ubud. A number of 135 completed questionaires analysed using Important-Performance Analysis. The results showed that there were twelve (12) factors considered very important by the customers and the performance of the restaurants was high; thirteen (13) factors were considered not important by the customers and the peformance of the restaurants was low; two (2) factors were considered not important by the customers but the performance of the restaurants was high; and there were no factors considered to be important by the customers but had low performance.